Persepsi Mahasiswa PPKn Terhadap Efektitivitas Kurikulum Merdeka dalam Membentuk Karakter Bangsa - Windi Hartati (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This study aims to investigate the perspectives of Pancasila and Citizenship Education (PPKn) students on the effectiveness of the Merdeka Curriculum in fostering student character. Employing survey methods and qualitative analysis, data were gathered from students at Sultan Ageng Tirtayasa University. The findings reveal that students possess a strong awareness of the Merdeka Curriculum, which they view as having a beneficial effect on their educational experiences. They report feeling more engaged in the learning process, particularly through project-based activities that promote collaboration and independence. Additionally, students acknowledge the curriculum's role in character development, highlighting improvements in communication skills and self-confidence. Nevertheless, the study also identified various challenges, such as maintaining consistent motivation for learning and balancing character development with academic performance. To address these issues, it is recommended that the curriculum be tailored to local contexts and that there be enhanced collaboration among schools, parents, and the community. These results underscore the significance of a holistic and contextual approach to education in enhancing the quality of education in Indonesia.